Urgensi Penelitian Tindakan Kelas Bagi Peningkatan Profesionalitas Guru Antara Cita Dan Fakta - Zetty Azizatun Ni’mah (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2017)
Professional teachers are required to have special skills and expertise in the field of teacher training in pedagogy, social, personal or professional competence so that the able to perform his duties and functions as a teacher. Ideality of classroom action research (PTK) as a medium to improve teacher professionalism in reality is not as expected, because there are still many problems found in the implementation of PTK for teachers. This constraint can be a lack of understanding of teachers on how to implement and write a PTK, the schedule of teachers who are so busy that had not time to do research, teachers thought that the PTK is difficult and some teachers who do not understand the benefits of the implementation of PTK for teachers, students or school institutions. Ideality of PTK implementation that has benefit in improving the quality of teaching and learning activities and increasing the professionalism of teachers is just a goal that is far from expectations that require solutions from various parties.